Pengembangan E-Modul Berbasis STEAM untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi Pada Pembelajaran Tematik di Sekolah Dasar - Pratiwi Kartika Sari*; Sutihat Sutihat (Jurnal Pendidikan Sains Indonesia, 2022)
The development of the world of education and technology has given birth to many challenges and real world problems to be faced. Students are required to utilize all their potential in a learning activity such as being able to build, synthesize, describe, evaluate, and create something from the knowledge they have into new knowledge in order to solve real-world problems. STEAM-based learning encourages students to explore their abilities. The development of a teaching material product in the form of a STEAM-based electronic module with the aim of improving higher-order thinking skills in high-grade thematic learning. This research is a development research, The model used in this research is the Dick and Carey development model. The validation results obtained from media experts are 82%, language is 89% and material is 84%, it can be said that the product developed is very feasible and can be tested. The next stage is a one to one trial, small group and field trials. The one to one trial got a score of 85% and the small group got a score of 90%. After that, entering the field trial, the results obtained were analyzed using the paired sample t-test. Before analyzing the data using the paired sample t-test, prerequisite tests were carried out, namely normality test and homogeneity test. The normality test obtained a result of 0,051, significance value 0.000. It can be stated that the STEAM-based electronic module can improve the higher-order thinking skills of high-class students